Clean label fresh sausage: characteristics throughout its shelf life - Paula Regina Rabelo Sbardelotto; Marina Leite Mitterer-Daltoé; Evellin Balbinot-Alfaro; Alfredo Jorge Costa Teixeira; Alexandre da Trindade Alfaro (Scientia Agricola, 2024)
ABSTRACT Consumers are increasingly demanding meat products that are natural and synthetic additive-free. This study aimed to develop a fresh pork sausage without synthetic additives and to evaluate the effects of this formulation on its physicochemical, microbiological, and sensory characteristics throughout its shelf life. Six formulations were prepared: FC = control formulation; F1 = celery extract (0.7 %) and rosemary extract with curry (0.06 %); F2 = celery extract (1 %) and rosemary extract with curry (0.06 %); F3 = celery extract (0.7 %) and rosemary extract with curry (0.1 %); F4 = celery extract (1 %) and rosemary extract with curry (0.1 %); F5 = celery extract (0.85 %) and rosemary extract with curry (0.08 %). The formulations with plant extracts exhibited a lower (p < 0.05) sodium content, and no differences (p > 0.05) were observed in the levels of lipid oxidation compared to FC. No direct relation was observed between the concentration of added celery extract and the residual nitrite content. Fresh sausage with plant extracts demonstrated a microbiological pattern like the control formulation during storage. The sensory acceptance of the formulations with plant extracts was similar to that of FC. The fresh sausages containing plant extracts showed characteristics like those of the conventional product, with these similarities becoming more pronounced throughout storage.